Feasibility and acceptability of a remotely‐delivered behavioural health coaching intervention to limit gestational weight gain - J. W. Coughlin; L. M. Martin; J. Henderson; A. T. Dalcin; J. Fountain; N.‐Y. Wang; L. J. Appel; J. M. Clark; W. Bennett (Wiley, 2020)
Summary Introduction Gestational weight gain (GWG) and postpartum weight retention (PPWR) are significant, potentially modifiable, contributors to women's future weight and health trajectories. There is a need for feasible and patient‐centered (i.e., convenient, remotely‐delivered, technology‐enhanced, and accessible through the prenatal care setting) behavioural interventions that limit GWG and PPWR. This study tests the feasibility and acceptability of a remotely‐delivered behavioural health coaching intervention to limit gestational weight gain and postpartum weight retention. Methods Pregnant women (11-16 weeks gestation) were recruited from two prenatal clinics and randomized to the active intervention or health education comparison group. Completion of the program was monitored and perceived helpfulness was rated (0-100). Results Twenty‐six women were randomized (n = 13 per arm; mean age = 31.6 years, SD = 3.6; mean BMI = 26.7 kg/m2, SD = 7.4). Participants completed a median of 18 coaching calls and 16/19 learning activities during pregnancy, and a median of 6 calls and 5/6 learning activities postpartum. They logged weights at least once/week for a median of 36/38 expected weeks and tracked daily calories and exercise for a median of 154/266 days and 72/266 days, respectively. Median (Q1, Q3) helpfulness ratings of the program during pregnancy were 80 (64, 91) and 62 (50, 81) postpartum; helpfulness ratings of coaching calls were 85 (58, 98). At 37 weeks gestation, 77% of participants achieved IOM weight gain recommendations compared to 54% in the comparison group. Conclusions This study provides evidence for the feasibility and acceptability of a remotely‐delivered behavioural weight control intervention in pregnancy and postpartum.